2003
DOI: 10.1046/j.1460-9568.2003.02595.x
|View full text |Cite
|
Sign up to set email alerts
|

A hot spot for hotfoot mutations in the gene encoding the δ2 glutamate receptor

Abstract: The orphan glutamate receptor delta2 is selectively expressed in Purkinje cells and plays a crucial role in cerebellar functions. Recently, ataxia in the hotfoot mouse ho4J was demonstrated to be caused by a deletion in the delta2 receptor gene (Grid2) removing the N-terminal 170 amino acids of the delta2 receptor. To understand how delta2 receptors function, we characterized mutations in eight additional spontaneously occurring hotfoot alleles of Grid2. The mouse Grid2 gene consists of 16 exons, spanning appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…In total, 11 recessive mutations abolishing grid2 expression were analysed at the molecular level. Among them, nine result from deletions of one or more exons and one corresponds to the spontaneous integration of an exogenous DNA sequence (Figure 2b) (Lalouette et al, 2001;Wang et al, 2003). Interestingly, all the mutations lie in the part of grid2 that is especially prone to breakage (Figure 1c, Figure 2d).…”
Section: Discussionmentioning
confidence: 99%
“…In total, 11 recessive mutations abolishing grid2 expression were analysed at the molecular level. Among them, nine result from deletions of one or more exons and one corresponds to the spontaneous integration of an exogenous DNA sequence (Figure 2b) (Lalouette et al, 2001;Wang et al, 2003). Interestingly, all the mutations lie in the part of grid2 that is especially prone to breakage (Figure 1c, Figure 2d).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, of the 20 alleles known so far, most mutants retain mutant GluR␦2 in the endoplasmic reticulum, indicating that GluR␦2 must be transported to the Purkinje cell surface for it to function properly (14,15,21). In addition, we recently demonstrated that the application of an antibody against the extracellular domain of GluR␦2 induced endocytosis of the AMPA receptor GluR2 and inhibited further induction of LTD (17).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although 50 -70% of the iGluRs are detected in the intracellular compartments of neurons (12,13), GluR␦2 is predominantly expressed at the cell surface (14). Interestingly, in the ataxic mutant mice hotfoot-4J, -7J, -11J, and -12J, GluR␦2 failed to be transported to the cell surface (14,15), which suggests that efficient trafficking of GluR␦2 to the cell surface is essential for its functioning in the cerebellum. Furthermore, GluR␦2 is not only transported to the Purkinje cell surface but also to spine regions where parallel fibers form synapses (16).…”
mentioning
confidence: 99%
“…Recently, the genes responsible for those mutants have been identified and include missense mutations, nonsense mutations or frameshift mutations in the causative genes. The hotfoot mice are spontaneously occurring recessive mutants (Guastavino et al, 1990) that carry mutations in Grid2, which encodes the 2 glutamate receptor (GluR2) (Wang et al, 2003). To date, more than 10 mutant alleles have been identified; among these, hotfoot5J mice have been shown to carry a point mutation in exon 12 of Grid2, which creates a stop codon in the region encoding transmembrane 3 of GluR2 protein (Wang et al, 2003).…”
Section: Disorders Of the Cerebellummentioning
confidence: 99%
“…The hotfoot mice are spontaneously occurring recessive mutants (Guastavino et al, 1990) that carry mutations in Grid2, which encodes the 2 glutamate receptor (GluR2) (Wang et al, 2003). To date, more than 10 mutant alleles have been identified; among these, hotfoot5J mice have been shown to carry a point mutation in exon 12 of Grid2, which creates a stop codon in the region encoding transmembrane 3 of GluR2 protein (Wang et al, 2003). The aberrant GluR2 protein is easily degraded and is not detected in Purkinje cells of hotfoot5J mice; therefore, hotfoot5J mice are mutants lacking GluR2 function.…”
Section: Disorders Of the Cerebellummentioning
confidence: 99%